2020
DOI: 10.22271/chemi.2020.v8.i3ag.9550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bio-inoculant, organic manure and chemical fertilizer on growth and yield of wheat (Triticum aestivum L.)

Abstract: An experiment was conducted during Rabi season 2018-19 at Instructional Farm, BTC College of Agriculture and Research Station, Bilaspur to to study the effect of bio-inoculant, organic manure and chemical fertilizer on growth and yield of wheat (Triticum aestivum L.). The wheat (var. CG-1013) was grown and treatments were replicated three times in randomized block design. The experiment consists of twelve treatments viz., 100% RDF (T1), 75% RDF (T2), 75% RDF + FYM @ 5 t ha -1 (T3), 75% RDF + Azotobacter (T4), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Residual effect of 75% and 100% recommended level of fertilizer in sorghum significantly increased plant height and number of tillers/plant of succeeding wheat (Patidar and Mali, 2002). Thakur et al, (2020) found that the application of 100% RDF (120 kg N + 60 kg P 2 O 5 + 40 kg K 2 O/ha) recorded higher spike length, test weight, grain and straw yield of wheat as compared to 75% RDF + FYM @5 t/ha + Azotobacter + PSB.…”
Section: Growth Yield Attributes and Yieldmentioning
confidence: 94%
“…Residual effect of 75% and 100% recommended level of fertilizer in sorghum significantly increased plant height and number of tillers/plant of succeeding wheat (Patidar and Mali, 2002). Thakur et al, (2020) found that the application of 100% RDF (120 kg N + 60 kg P 2 O 5 + 40 kg K 2 O/ha) recorded higher spike length, test weight, grain and straw yield of wheat as compared to 75% RDF + FYM @5 t/ha + Azotobacter + PSB.…”
Section: Growth Yield Attributes and Yieldmentioning
confidence: 94%
“…The highest yield of grain (~53 q ha −1 ) and straw (~74 q ha −1 ) was noted with the highest dose of fertilizer, i.e., 100% NPK along with composite bio-inoculants (PGPR + Glomus fasciculatum). The application of all inorganics, organic fertilizer, and various bio-inoculants might supply available nutrients and increase soil health [59][60][61]. Enhanced yield with compost and fertilizer; bio-inoculants and fertilizer might be owing to an increased supply of plant nutrients [50,62,63].…”
Section: Effect On Interactionmentioning
confidence: 99%